LANGUAGE ECOLOGY AND DOMAIN: COMPARISON BETWEEN SASAK AND BAJO LANGUAGE RESISTANCE IN LOMBOK (EKOLOGI DAN RANAH BAHASA: KOMPARASI KEBERTAHANAN BAHASA SASAK DAN BAHASA BAJO DI LOMBOK) - Khirjan Nahdi; Usuluddin Usuluddin; Moh. Irfan; Lalu Mas’ud (Universitas PGRI Sumatera Barat, 2021)
This study aims to map the choice of Sasak and Bajo languages by their respective speakers and to map land and sea ecology trends in both. The language ecology is a reference for the thinking of this study, considering the language ecology is related to the thoughts of language speakers and the context of language use. In addition to the concept of language ecology, the concept and study of language survival in several contexts of language use are the reference of this study. Through participatory survey methods and content analysis it was found that the Bajo language was more consistent in the realms of communication than the Sasak language. This condition is proven by the portion of Bajo language usage which is always more dominant in all domains compared to other languages. Both of the phenomena above show that marine ecology is very strategic in supporting the survival of the Bajo language in the sphere of communication of its speakers. On the other hand, terrestrial ecology with its various dynamics causes the inconsistency of Sasak speakers to maintain the language of Sasak in some domains.